THE EXPRESSIVENESS OF THE CHARACTERS IN THE PROCESS OF CREATING NEW VARIETIES OF VINES - Eugeniu ALEXANDROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the present article are reflected in results of the study about of resveratrol the concentration the juice berries of vine varieties both at the wild and how the culture. As the object of study having served: Muscadinia rotundifolia Michx. and varieties of interspecific hybridization results obtained with Vitis vinifera L. subsp. D.C. sativa, Vitis vinifera L. subsp. sylvestris C.C. Gmel., varieties of vine cultivation. Conducted a comparative analysis about the expressiveness of of resveratrol species of wild the vines and how the expresses the chemical compounds to progeny obtained as a result of hybridization. As a result of the researches it was concluded that the concentration of resveratrol species of wild vine is much larger, nearly double as compared to the descendants of these species and how it are advancing in generations, ie removing us from wild species the concentration of resveratrol decreases in the juice berries of vine.